Ziarah Wali Sebagai Tradisi Santri (Studi Terhadap Tradisi Ziarah Kubur Makam Sayyid Yusuf) - Ahmad Jubaidi (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
The reality in the field where people make religious pilgrimages causes the author's interest in researching the tradition of the grave pilgrimage of the scholar of Allah SWT. which exists among the community today. The issues raised from this research are how the community practices the grave pilgrimage of Sayyid Yusuf's grave? and how the santri traditionalise the grave pilgrimage of Sayyid Yusuf's grave? Considering that in Pesantren the santri are encouraged to frequent a pilgrimage to the grave of the founding figures of the pesantren. Therefore, the author wants to prove that the community tradition of pilgrimage to the grave of Allah Swt. scholar is part of the santri tradition. In this research, the author utilizes a qualitative research method with the a case study approach. This method is a type of research method that has more characteristics to examine social and cultural phenomen naturally. The results of this study are, first, people perform grave pilgrimages, especially to Sayyid Yusuf with the aim of connecting prayers to the saints of God. They assume that saints are God's chosen people and must be close to Him. In addition, the practice of pilgrimage can make pilgrims feel calm, peaceful, safe and serene. Second, the pilgrimage to the grave of Sayyid Yusuf's grave is not only done to visit the grave, but to read the Qur'an, expect blessings and tawasul. Third, grave pilgrimage can be categorised as a santri tradition that is also practised among the community.